Theorizing is for everybody: Advancing the process of theorizing in implementation science - Meza, Rosemary D.; Moreland, James C.; Pullmann, Michael D.; Klasnja, Predrag; Lewis, Cara C.; Weiner, Bryan J. (Frontiers in Health Services, 2023)
There has been a call to shift from treating theories as static products to engaging in a process of theorizing that develops, modifies, and advances implementation theory through the accumulation of knowledge. Stimulating theoretical advances is necessary to improve our understanding of the causal processes that influence implementation and to enhance the value of existing theory. We argue that a primary reason that existing theory has lacked iteration and evolution is that the process for theorizing is obscure and daunting. We present recommendations for advancing the process of theorizing in implementation science to draw more people in the process of developing and advancing theory.